Analisis 3-Monokloro-1,2-Propanadiol (3-MCPD) Ester dalam Minyak Sawit dengan Instrumen Kromatografi Gas-Spektroskopi Massa - Hanifah Nuryani Lioe; Nancy Dewi Yuliana; Dias Indrasti; Yane Regiyana; Cony Arisya Putri (Jurnal Ilmu Pertanian Indonesia, 2015)
A group of components called as 3-monochloropropane-1,2-diol (3-MCPD) esters has been found in some vegetable oils, particularly palm oil. Analysis of these components needs GC-MS instrument to reach a low level detection, parts per billion or ppb level. An effort to validate the 3-MCPD esters analysis by GC-MS method (Weiβhaar method) using phenyl boronic acid (PBA) as a derivatizing agent and isotopic internal standard (IS) 3-MCPD-D5 followed by the determination of 3-MCPD in commercial palm oils has been conducted. The analytical results showed the instrumental performance as follows: instrument linearity for the analysis of 3-MCPD standard solutions containing IS 2.0 μg/mL was obtained at a concentration range of 0.25-7.50 μg/mL test solution with R2 higher than 0.990, precision of 3-MCPD as well as IS retention time was less than 2.0% which was acceptable according to JECFA guidance. Instrument detection limit (LOD) and limit of quantitation (LOQ) were read from GC-MS based on the linearity experiment, i.e. 0.17 and 0.59 μg/mL solution, respectively. Method linearity by using palm oil as a matrix also showed R2 higher than 0.990. Recovery test result at 40 μg/g gave an accuracy at 83.29 ± 7.12% which is in the range of AOAC standard (80-110%) and precision at 5.38% (less than RSDHORWITZ). Analysis of 14 palm oils from local market showed 100% of the sampels were positive to contain 3-MCPD esters. 3-MCPD esters in palm oil were found at a concentration range of 8.15-58.14 µg 3-MCPD/g sample.